Peranan dan Model Evaluasi dalam Kurikulum Pendidikan Agama Islam - Burhanuddin, Burhanuddin; Husnia, Husnia; Ridho, Achmad Rasyid (TSAQOFAH, 2026)
Evaluation is an essential component of the Islamic Religious Education (PAI) curriculum because it serves to measure the achievement of educational objectives comprehensively, encompassing cognitive, affective, and psychomotor domains. This article aimed to examine the role of evaluation in the PAI curriculum and to describe various evaluation models that are relevant for supporting the implementation of PAI learning. The method employed was library research by analyzing books, scholarly journal articles, and educational policy documents related to evaluation and the PAI curriculum. The findings indicate that evaluation in the PAI curriculum functions not only as a tool to measure learning outcomes, but also as a means to improve the learning process and strengthen students’ character formation. Evaluation models such as formative, summative, authentic, and competency-based evaluation were identified as relevant approaches to ensure the comprehensive attainment of PAI objectives. The study concludes that the application of appropriate, systematic, and competency-oriented evaluation models contributes to the realization of effective PAI learning in shaping students who are faithful, morally upright, and broadly knowledgeable.